A reevaluation of the epimeric and anomeric relationship of glucosides and galactosides in thermotropic liquid crystal self-assemblies - Hashim, R.; Mirzadeh, S.M.; Heidelberg, T.; Minamikawa, H.; Yoshiaki, T.; Sugimura, A. (Elsevier, 2011)
Anomers and epimers alpha- and beta-gluco and -galactosides are expected to behave differently. However, recent results on a series of Guerbet glycosides have indicated similar liquid crystal clearing temperatures for pure p-glucosides and the corresponding alpha-galactosides. This observation has led to speculation on similarities in the self-assembly interactions between the two systems, attributed to the trans-configuration of the 4-OH group and the hydrophobic aglycon. Previous simulations on related bilayers systems support this hypothesis, by relating this clearing transition temperature to intralayer (sugar-sugar) hydrogen bonding. In order to confirm the hypothesis, the comparison was expanded to include the cis-configurated pair, that is, alpha-gluco/beta-galactoside. A set of alpha-configurated Guerbet glucosides as well as octyl alpha-galactoside were prepared and their thermotropic phase behavior studied. The data obtained enabled a complete comparison of the isomers of interest. While the results in general are in line with a pairing of the stereo-isomers according to the indicated cis/trans-configuration, differences within the pairs can be explained based on the direction of hydrogen bonds from a simple modeling study. (C) 2011 Elsevier Ltd. All rights reserved.